MIRZA ULUGBEK PATRON OF LITERATURE (The Journal of Interdisciplinary Human Studies, 2025)
In the development of world astronomical science, medieval oriental astronomy, including the activities of Central Asian scientists, holds a special place,. During this period, Central Asian scholars, especially Uzbek ones, left a very rich legacy concerning the theory of the motion of the Sun, Moon, and planets, as well as practical astronomical problems related to determining the geographical coordinates of time and place,. During this period, hundreds of great thinkers of Muslim countries were engaged in research in the fields of astronomy, mathematics, and philosophy.
Keywords: Movarounnar; fiction; thinker; astronomy; literary collection; scientific heritage; scientists; theory; applied astronomy